Consistent drivers of plant biodiversity across managed ecosystems - Minden, Vanessa; Scherber, Christoph; Cebrián Piqueras, Miguel A.; Trinogga, Juliane; Trenkamp, Anastasia; Mantilla-Contreras, Jasmin; Lienin, Patrick; Kleyer, Michael (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2016)
Ecosystems managed for production of biomass are often characterized by low biodiversity because management aims to optimize single ecosystem functions (i.e. yield) involving deliberate selection of species or cultivars. In consequence, considerable differences in observed plant species richness and productivity remain across systems, and the drivers of these differences have remained poorly resolved so far. In addition, it has remained unclear if species richness feeds back on ecosystem functions such as yield in real-world systems. Here, we establish N = 360 experimental plots across a broad range of managed ecosystems in several European countries, and use structural equation models to unravel potential drivers of plant species richness. We hypothesize that the relationships between productivity, total biomass and observed species richness are affected by management intensity, and that these effects differ between habitat types (dry grasslands, grasslands, and wetlands). We found that local management was an important driver of species richness across systems. Management caused system disturbance, resulting in reduced productivity yet enhanced total biomass. Plant species richness was directly and positively driven by management, with consistently negative effects of total biomass. Productivity effects on richness were positive, negative or neutral. Our study shows that management and total biomass drive plant species richness across real-world managed systems.